OBSTRUCTION OF JUSTICE DALAM PERKARA KORUPSI YANG DILAKUKAN OLEH ADVOKAT (STUDY KASUS PUTUSAN NO. 3/Pid.Sus-TPK/2022/PN.JMB): Obstruction Of Justice In Corruption Cases Conducted By Advocates (Case Study Decision Number 3/Pid.Sus-Tpk/2022/Pn.Jmb) - Nenchy Hotmauli; Nenchy Hotmauli Sinaga (Faculty of Law, Universitas Trisakti, 2025)
The present study examines the illegal act of Obstruction of Justice perpetrated by the defendant Tengku Ardiansyah in a corruption case, as evidenced by the defendant's activities in decision number 3/Pid.Sus-TPK/2022/PN. The identification problem: regarding the Republic of Indonesia Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption Crimes, are the defendant's actions considered Obstruction of Justice? Additionally, is it the case that Decision No. 3/Pid.Sus-TPK/2022/PN.JMB, which sentenced the defendant to prison, complied with Article 21 of the prior laws. This study is normative, descriptive, and analytical, and data were gathered online, from relevant laws and regulations, and published books written by legal professionals. The result and conclusion; defendant's acts, which include obstructing the course of justice, are governed in this instance by Article 21 of Law No. 31 of 1999 of the Republic of Indonesia, which is read in connection with Law No. 20 of 2001, which is about the decline of corruption crimes. When determining whether a conduct is criminal, the Jambi District Court follows the relevant laws and rules. Advocates must base their performance of their obligations on the related verdicts, provisions, and professional code of ethics—promoters who work as law enforcement officials ought to be in favor of ending criminal corruption.